Find the Taylor series for f(x) centered at the given value of a. [Assume that f has a power series expansion. Do not show that Rn(x) → 0.] f(x) = ln(x), a = 3 f(x) = ln(3) + ∞ n = 1 Find the associated radius of convergence R. R =

Respuesta :

Answer:

The Taylor series is [tex]\ln(x) = \ln 3 + \sum_{n=1}^{\infty} (-1)^{n+1} \frac{(x-3)^n}{3^n n}[/tex].

The radius of convergence is [tex]R=3[/tex].

Step-by-step explanation:

The Taylor expansion.

Recall that as we want the Taylor series centered at [tex]a=3[/tex] its expression is given in powers of [tex](x-3)[/tex]. With this in mind we need to do some transformations with the goal to obtain the asked Taylor series from the Taylor expansion of [tex]\ln(1+x)[/tex].

Then,

[tex]\ln(x) = \ln(x-3+3) = \ln(3(\frac{x-3}{3} + 1 )) = \ln 3 + \ln(1 + \frac{x-3}{3}).[/tex]

Now, in order to make a more compact notation write [tex]\frac{x-3}{3}=y[/tex]. Thus, the above expression becomes

[tex]\ln(x) = \ln 3 + \ln(1+y).[/tex]

Notice that, if x is very close from 3, then y is very close from 0. Then, we can use the Taylor expansion of the logarithm. Hence,  

[tex]\ln(x) = \ln 3 + \ln(1+y) = \ln 3 + \sum_{n=1}^{\infty} (-1)^{n+1} \frac{y^n}{n}.[/tex]

Now, substitute [tex]\frac{x-3}{3}=y[/tex] in the previous equality. Thus,

[tex]\ln(x) = \ln 3 + \sum_{n=1}^{\infty} (-1)^{n+1} \frac{(x-3)^n}{3^n n}.[/tex]

Radius of convergence.

We find the radius of convergence with the Cauchy-Hadamard formula:

[tex]R^{-1} = \lim_{n\rightarrow\infty} \sqrt[n]{|a_n|},[/tex]

Where [tex]a_n[/tex] stands for the coefficients of the Taylor series and [tex]R[/tex] for the radius of convergence.

In this case the coefficients of the Taylor series are

[tex] a_n = \frac{(-1)^{n+1}}{ n3^n}[/tex]

and in consequence [tex]|a_n| = \frac{1}{3^nn}[/tex]. Then,

[tex] \sqrt[n]{|a_n|} = \sqrt[n]{\frac{1}{3^nn}}[/tex]

Applying the properties of roots

[tex] \sqrt[n]{|a_n|} = \frac{1}{3\sqrt[n]{n}}.[/tex]

Hence,

[tex]R^{-1} = \lim_{n\rightarrow\infty} \frac{1}{3\sqrt[n]{n}} =\frac{1}{3}[/tex]

Recall that

[tex]\lim_{n\rightarrow\infty} \sqrt[n]{n}=1.[/tex]

So, as [tex]R^{-1}=\frac{1}{3}[/tex] we get that [tex]R=3[/tex].